Adherence to Anti-Hypertensive Drugs: A Clinic Based Study among Geriatric Hypertensive Patients in Rural, India - Sanjaya Kumar Sahoo; PS Preeti; Dhiraj Biswas (Medsci Publications, 2018)
Background: Hypertension is a common chronic health condition, more among the elderly and is the most important risk factor for all subtypes of vascular disease and death. A medication's success in producing the desired benefit depends on a person's adherence with the therapeutic regimen. The World Health Organization (WHO) describes poor adherence as the most important cause of uncontrolled blood pressure and estimates that 50% of people do not take their antihypertensive medication as prescribed. Objectives of this study were to assess the adherence to anti-hypertensive therapy and also to elicit the determinants of poor adherence among geriatric hypertensives. Methodology: An observational, cross-sectional, descriptive study was conducted among geriatric hypertensive attended the OPD during the study period in the rural health centre of West Bengal, India. Results: 44.63% of the respondents adhered to anti-hypertensive drugs . The most common reasons for poor adherence were due to irregular supply from government pharmacy (72.3%) followed by forgetfulness (67.5%) and non-affordability (66.3%).Poor adherence to drugs was significantly (p<0.05) associated with contextual variables like age, literacy, socio-economic status, duration of treatment and presence of comorbidities. Conclusion: Advocacy of adherence to antihypertensive drugs should be inculcated in each and every hypertensive patient along with regular and uninterrupted drug supply and high quality health care service in all health care organisations where health education and counselling gets the highest priority.